Filtration Tube Model Utilizing Coconut Husk for Domestic Wastewater Treatment: Oil Removal Method - Hajimi Hajimi; Moh Adib; Fara Chitra; Asmadi Asmadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The presence of oil and fat in household wastewater is a significant water pollutant, as it is typically disposed of without prior treatment. Coconut husks are a promising material that can be used as a filter medium. This study aimed to evaluate the effectiveness of coconut fiber filtration in the treatment of domestic wastewater. The study employed a quasi-experimental design with pre- and post-tests but no control group. Wastewater was passed through tubs filled with coconut husk. Three different filtration tub models were tested: Model A single baffle, Model B with three baffles, and Model C with no baffle. Oil content was monitored on the 3rd, 7th, 14th, 21st, and 28th days in milligrams per liter. A Kruskal-Wallis and Mann-Whitney test was conducted to compare the results of oil content reduction between filter models. The results revealed significant differences in the mean oil content reduction among the various tub models. The percentage of oil reduction reaches 95-99%. Furthermore, the Mann-Whitney test showed no significant difference between Models A and C. However, considerable differences were identified between Models A and C, as well as between Models B and C. In conclusion, this study provides evidence of the effectiveness of coconut husk filters in reducing oil levels, with nearly the maximum observed reduction achieved by the 28th day. Additionally, it is recommended to explore the long-term sustainability and potential applications of coconut husk filters in various oil removal scenarios.